Oil, Law, and Power: The Role of Commercial Legislation in Nigeria's Economic History (1960–2020) - Nnebuihe, Linda Iheanacho; Okoi, Ibiang (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This paper examines the complex interplay between oil wealth, commercial legislation, and economic power in Nigeria from 1960 to 2020, tracing how legal frameworks have shaped and been shaped by the country’s petroleum-dominated economy. Through historical and legal analysis, the study explores three distinct phases: the foundational period (1960–1979), which established Nigeria’s oil legal regime; the era of military rule (1980–1999), characterized by the militarization of commercial law; and the democratic period (2000–2020), marked by attempted reforms amid persistent governance challenges. Drawing on primary sources including legislation, court rulings, and oil contracts, as well as secondary literature on political economy, the paper argues that Nigeria’s commercial legislation has served as both an instrument of economic management and a reflection of broader power dynamics. The analysis reveals how oil dependency has distorted legal development, creating a system where laws often prioritize elite interests and foreign corporations over sustainable development. Comparative insights from Norway, Indonesia, and Angola highlight alternative approaches to resource governance, while policy recommendations propose pathways for legal reform. The study contributes to broader debates about law, resource dependence, and economic development in petrostates, offering critical lessons for Nigeria and other resource-rich developing nations.